THE IMPORTANCE OF EFFECTIVE CORPORATE GOVERNANCE IN COMPANIES PARTICIPATING IN THE CAPITAL MARKET - Karimov Akramjon Ikromjon ugli; Boysunov Jamshid Baxriddin ugli; Razzoqova Jumagul Rasulbek qizi; Yakhshiboyev Jahongir Abdualimovich (Scholar Express Journals, 2025)
This article highlights the importance of effective corporate governance in companies participating in the capital market, emphasizing its role in ensuring transparency, investor protection, and sustainable value creation. In an increasingly competitive and regulated financial environment, strong corporate governance structures are essential to enhancing a company’s credibility, market performance, and access to capital. The study explores key governance mechanisms, including the composition and independence of boards, accountability of executive management, disclosure standards, and the protection of shareholder rights. It also examines how corporate governance influences investor confidence, reduces capital costs, and minimizes agency risks. Through comparative analysis and case studies from both developed and emerging markets, the article identifies best practices that align governance frameworks with long-term strategic goals. The findings suggest that companies with robust governance practices are more likely to achieve higher market valuation, improved liquidity, and greater resilience to financial shocks. The article concludes by recommending policy measures and strategic initiatives to strengthen governance practices, especially for joint-stock companies seeking to maximize their presence in the capital market.
Keywords: Corporate Governance; Capital Market; Joint-Stock Companies; Board Of Directors